Evaluation du l’activité anti-inflammatoire de bioglucumin-mélange de deux extrais des plantes médicinales : (Mushroom et Curcumine) "Étude expérimentale in vivo chez la souris (NMRI)" - Rezkallah, Zeyneb (My University, 2018)
Many plants are known for their use in traditional medicine for the treatment of several diseases including inflammatory component diseases. The present study aims to study the anti-inflammatory effects of a mixture of two medicinal plants: Mushroom and curcumin (bioglucumine). The experiments were performed on the model of acute edema of the paw induced by carrageenan mice. The model was tested by aqueous extracts of bioglucumin at doses of 50, 100 and 150 mg / kg administered orally. Gavage was performed one hour before induction of acute inflammation with 1% carrageenan. The results obtained were compared with those of Diclofenac and those of physiological control. After oral administration of physiological saline, carrageenan significantly increased mouse paw volume by 71.97 ± 15.06%, 51.06 ± 4.46%, and 33.92 ± 19.46%, respectively. 1h, 3h and 6h. Administration of Diclofenac (50 mg / kg, oral) significantly prevented the increase in mouse paw volume of 64.77 ± 26.88%; 15.29 ± 8.37%; 0.51 ± 0.59 respectively at 1h, 3h and 6h after administration of carrageenan. Oral administration of the aqueous extract of bioglucumin at the dose of 50 mg / kg significantly prevents acute edema of the paw of the mice after 1 h, 3 h and 6 h; the percentages of increase in the volume of the paw are respectively 55.93 ± 4.59%; 15.82 ± 2.91%; 0 ± 0% at a dose of 100mg / kg 38.35 ± 15.67%; 15.32 ± 5.08%; 0 ± 0% The histological study of sections treated with Diclofénac and aqueous extract of bioglucumin (50, 100 and 150 mg / kg) confirm that these treatments have anti-inflammatory activity. In addition, at a dose of 100 mg / kg, the inflammatory infiltrate disappears almost completely. The results of this study highlight the pharmacological bases of bioglucumin in traditional medicine to prevent inflammatory processes
Keywords: Bioglucumin; Mushroom; Curcumine; Extrait aqueux; Odème.; bioglucumin; Mushroom; curcumin; anti-inflammatory; edema; aqueous extract.